Acute Esophageal Necrosis and Low-Flow State - Ahmad Burtally; Philippe Gregoire (Canadian Journal of Gastroenterology)
Acute esophageal necrosis (AEN), also called black esophagus, is quite exceptional. Endoscopic findings show circumferential black discolouration of the esophagus with or without exudates. The etiology of AEN is presently unknown and is assumed to be multifactorial. Distal esophageal involvement with proximal extension ending sharply at the gastroesophageal junction is the most common presentation. The present case report describes the clinical and endoscopic evolution of black esophagus observed in a patient with significant peripheral vascular disease, who was presented to the intensive care unit at the Hopital Saint-Francois d’Assise (Quebec City, Quebec). Through an extensive review of the literature, common underlying clinical conditions of patients diagnosed with AEN have been identified.